Understanding Barotrauma in Fish Passing Hydro Structures: A Global Strategy for Sustainable Development of Water Resources. Issue 3 (21st March 2014) - Brown, Richard S.; Colotelo, Alison H.; Pflugrath, Brett D.; Boys, Craig A.; Baumgartner, Lee J.; Deng, Z. Daniel; Silva, Luiz G. M.; Brauner, Colin J.; Mallen‐Cooper, Martin; Phonekhampeng, Oudom; Thorncraft, Garry; Singhanouvong, Douangkham
ABSTRACT: Freshwater fishes are one of the most imperiled groups of vertebrates, and population declines are alarming in terms of biodiversity and to communities that rely on fisheries for their livelihood and nutrition. One activity associated with declines in freshwater fish populations is water resource development, including dams, weirs, and hydropower facilities. Fish passing through irrigation and hydro infrastructures during downstream migration experience a rapid decrease in pressure, which can lead to injuries (barotrauma) that contribute to mortality. There is renewed initiative to expand hydropower and irrigation infrastructure to improve water security and increase low‐carbon energy generation. The impact of barotrauma on fish must be understood and mitigated to ensure that development is sustainable for fisheries. This will involve taking steps to expand the knowledge of barotrauma‐related injury from its current focus, mainly on seaward‐migrating juvenile salmonids of the Pacific Northwest, to incorporate a greater diversity of fish species and life stages from many parts of the world. This article summarizes research that has examined barotrauma during fish passage and articulates a research framework to promote a standardized, global approach. The suggested approach provides clearly defined links to adaptive development of fish friendly technologies, aimed at mitigating the threats faced by global freshwater fisheries from the rapid expansion of water infrastructure.